2008
DOI: 10.1182/asheducation-2008.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Nocturnal Hemoglobinuria: An Historical Overview

Abstract: The clinical hallmark of paroxysmal nocturnal hemoglobinuria (PNH) is episodic hemoglobinuria, and it was this feature that captured the attention of European physicians in the latter half of the 19th century, resulting in careful observational studies that established PNH as an entity distinct from paroxysmal cold hemoglobinuria and march hemoglobinuria. Curiosity about the etiology of the nocturnal aspects of the hemoglobinuria led the German physician Paul Strübing to develop the prescient hypothesis that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
0
23
0
1
Order By: Relevance
“…1 The discoveries began with the seminal observations of Thomas Hale Ham in the late 1930s that suggested a novel, antibody-independent mechanism for complement activation. Subsequently, Ham's observations contributed to elucidation of the properdin pathway (now known as the alternative pathway) by Louis Pillemer while the two were on the faculty at Case Western Reserve University in the 1950s.…”
Section: Introductionmentioning
confidence: 99%
“…1 The discoveries began with the seminal observations of Thomas Hale Ham in the late 1930s that suggested a novel, antibody-independent mechanism for complement activation. Subsequently, Ham's observations contributed to elucidation of the properdin pathway (now known as the alternative pathway) by Louis Pillemer while the two were on the faculty at Case Western Reserve University in the 1950s.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Various mechanisms have been evoked to explain its physio-pathology. It seems that continuous activation of complement at the platelets surface will produce release of thrombinogen particules enriched in phosphatidylserine which can fix factor V and prothombinase complexes.…”
Section: Discussionmentioning
confidence: 99%
“…[1] This is a rare disease (1.3 cases per million individuals ) expressed predominantly in young (median age 32) caucasian people. Recent studies have shown that the disease was related to an acquired mutation of hematopoietic stem cell on phosphatidyl-inositol glycan (GPI) class A (PIG-A) gene located on X chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…Casos compatíveis com HPN já haviam sido relatados em 1793, porém a descrição da doença como síndrome clínica foi feita apenas em 1882 por Paul Strubing 5 . O epônimo síndrome de MarchiafavaMicheli caiu em desuso pelo relato tardio e pequena contribuição destes autores para o entendimento da doença 6 . O termo hemoglobinúria paroxística noturna refere-se à descrição de destruição de eritró-citos com liberação de hemoglobina na urina, notada principalmente por coloração marrom-escura na primeira urina da manhã 7 .…”
Section: Artigo De Revisão Introduçãounclassified